STUDIES ON THE PLANKTON OF MEXICO - TAFALL OSORIO, B F (Rockefeller Foundation, CD MEXICO, DF, MEX, 1943)
Blood and organ smears of 102 birds from the Mexican states of Nuevo Leon and Tamaulipas were examined They represented 65 genera and 79 spp 14 spp were found parasitized by Haemoproteus, 5 by Leu-cocytozoon, 5 by Plasmodium, 2 by Trypanosoma, and 1 (p
CIENC MEX
Keywords: STUDIES, PLANKTON, MEXICO; MULTIDISCIPLINARIA; BIOLOGIA VEGETAL; BOTANICA GENERAL